Food management innovations for reducing food wastage - a systematic literature review - Żmieńka, Ewa; Staniszewski, Jakub (Zielona Góra: Faculty of Economics and Management Press)
The goal of this paper is to assess the current trends in research on food waste management innovations in social sciences and mapping them. To achieve this, 107 articles were extracted from the Web of Science database with the keywords food waste and innovations/technologies. Then, we grouped them in accordance with part of supply chain they concern and type of innovation they propose. We identified that the majority of the innovations concern the final stages of the food supply chain.
Keywords: food waste; food chain; innovation; systematic literature review; marnotrawstwo żywności; łańcuch dostaw; innowacje; systematyczny przegląd literatury